José A. Canongia, Joaquim Casimiro, Karol Kurpinski, António Saiote (clarinete), Orquestra Clássica do Porto, dir. Manuel Ivo Cruz - Mendes, Nuno Bettencourt (Revista Portuguesa de Musicologia, 2014)
Recensão: José A. Canongia, Joaquim Casimiro, Karol Kurpinski, António Saiote (clarinete), Orquestra Clássica do Porto, dir. Manuel Ivo Cruz